Anaerobic digestion of tannery solid waste by mixing with different substrates (Bangladesh Journal of Scientific and Industrial Research, 2015)
The tannery solid waste (fleshing) was collected from Hazaribagh, Dhaka. It has been found that fleshing contains 82.57% volatile matter. Further characterization of fleshing showed that it contains low C/N ratio of 2.64 and high pH of 10.99. These characteristics were not suitable for using fleshing as a substrate for anaerobic digestion. The study has been carried out in different ratio of waste fleshing, domestic sewage and cow dung at total solid 6% concentration. In all the reactors fleshing and domestic sewage were mixed at 1:1 ratio. On the basis of the performance of the reactors it was evident that the reactor which contains 75% fleshing with domestic sewage and 25% cow dung showed optimum result. Under optimum condition volatile solids destruction 52%, specific gas production 0.476 L/g volatile solids feed and methane yield 73% were achieved. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22006 Bangladesh J. Sci. Ind. Res. 49(2), 119-124, 2014